ALMA observation of the disruption of molecular gas in M87. Issue 3 (9th January 2018) - Simionescu, A; Tremblay, G; Werner, N; Canning, R E A; Allen, S W; Oonk, J B R
Abstract: We present the results from Atacama Large Millimeter Array (ALMA) observations centred 40 arcsec (3 kpc in projection) south-east of the nucleus of M87. We report the detection of extended CO (2–1) line emission with a total flux of (5.5 ± 0.6) × 10 −18 erg s −1 cm −2 and corresponding molecular gas mass $M_{{\rm H}_2}=(4.7 ± 0.4) × 10^5 \, M_{\odot }$, assuming a Galactic CO to H2 conversion factor. ALMA data indicate a line-of-sight velocity of −129 ± 3 km s −1, in good agreement with measurements based on the [C ii ] and H α+[N ii ] lines, and a velocity dispersion of σ = 27 ± 3 km s −1 . The CO (2–1) emission originates only outside the radio lobe of the active galactic nucleus (AGN) seen in the 6 cm Very Large Array image, while the filament prolongs further inwards at other wavelengths. The molecular gas in M87 appears to be destroyed or excited by AGN activity, either by direct interaction with the radio plasma, or by the shock driven by the lobe into the X-ray emitting atmosphere. This is an important piece of the puzzle in understanding the impact of the central AGN on the amount of the coldest gas from which star formation can proceed.